Energy reduction of building air-conditioner with phase change storage - Nattaporn Chaiyat (2018)
© Research India Publications. In this study, a concept of using phase change material (PCM) for improving cooling efficiency of an air-conditioner has been presented under Thai climate. Rubitherm20 (RT-20) is selected to evaluate the thermal performance by reducing the air temperature entering the evaporating coil. The model of PCM celluloid balls have been performed with the air-conditioner. Moreover, the mathematical model of the air-conditioner with the PCM storage is developed and verified with the testing results. For the experiment, 2 TR of R-134a airconditioner is chosen to test a pack bed of PCM balls with thickness 20 cm, 30 cm and 40 cm. And the pressure drops of the air flowing through the bed are considered with and without a set of by-pass tubes along the height of the storage bed. From the study results, it could be seen that pressure drops of the bed with and without bypass tubes are nearly the same results. Thus, PCM ball pack bed using RT-20 without bypass tubes is used to improve the cooling efficiency of air-conditioner. And the testing results, it could be found that the compressor could be stopped when the PCM balls absorb heat from the hot air before entering the evaporator coil. Moreover, the experimental result of the modified unit is compared with the simulation data to verify the mathematical model for predicting the cooling performance of the PCM bed combined with the air-conditioner. It could be seen that the simulated data of the PCM temperature and the air leaving PCM bed temperature agree quite well with the experimental result at the discrepant around 2.73% and 4.61%, respectively.Finally, the model is used to analyze the economic result which is found that the electrical consumption of the modified air-conditioner could be decreased around 3.09 kWh/d. When the electrical power consumption of the modified unit is around 36.27 kWh/d at the operating time 15 h/d compared with around 39.36 kWh/d of the normal unit at the operating time 12 h/d. The saving cost from the PCM bed could be 9.10% or 170.03 USD and the payback period is around 4.15 y.